The efficiency improvement for traffic operating and modifying delay time in al-Kadessah intersection at AL Ramadi city - Mhana, Khalid (Iraqi Journal of Civil Engineering, 2024)
Traffic movement is considered a compound phenomenon that is impacted by behavioural, economic, and physical aspects. It is performed within the context of an urban system that consists of road networks and crossings, where the movement crouches to depend. The measuring of identifying their size and densities and current problems helps to Improve and development for roads and streets network existing and important is intersections for purposes the accessibility, potentiality of future intersections, and network development towards constructing a composition to raise the quality and the efficient performance of roads and streets. The study was dependent on a traffic survey for intersections, areas of urban intersections, and the road network of Al-Ramadi city, as well as the number of vehicles that generated a large volume of traffic flow. The use of the program (HCS 2010) to detect appropriate for purposes decreasing traffic congestion and delayed trip time in the areas based on existing and future districts that generate different types and purposes of journeys to lessen the delay trip time to lessen traffic congestion. Therefore, research looks at both sides: first, a study of the existing intersections of the main road network and urban streets, including an examination of the components and shapes of these intersections in the study area; second, an examination of the importance placed on these intersections by the planning and design process.